Pelaksanaan Program Screning Kanker Cerviks dengan Pemeriksaan Inspeksi Visual Asetat di Desa Tambakagung, Kecamatan Puri, Mojokerto Jawa Timur - Kurnia Indriyanti Purnama Sari; Kiftiyah Kiftiyah; Nuris Kushayati (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
A reproductive health problem of concern worldwide, especially among women, is cervical cancer. Cervical cancer is the second leading cause of cancer-related death in women worldwide (Ministry of Health, Republic of Indonesia, 2019). According to a 2018 WHO report, an estimated 529,828 women are diagnosed with cervical cancer and 275,128 die each year. This high mortality rate is due to delayed treatment, as more than 70% of cases are in the advanced stage (Prabasari & Budiana, 2017). Screening for cervical cancer with IVA includes visual examination of the cervix using vinegar (3-5%). A community service was held at the STIKES Dian Husada Mojokerto Campus Laboratory. The IVA trial activity was conducted on his 9 June 2022 with his 18 participants. Procedures for this non-commercial service include coordinating with stakeholders, conducting initial interactions for non-commercial activities, conducting a partner needs analysis, preparing to administer the IVA test, and completing the IVA test. Based on studies in women of childbearing age, the results were negative. Therefore, IVA testing has been successfully implemented to improve the health and awareness of women of childbearing age as a tool for early detection of cervical cancer.Keywords: Screening Examination, Cervical Cancer, IVA